Continuity of care in general practice vocational training: prevalence, associations and implications for training. Issue 1 (2nd January 2016) - Pearlman, James; Morgan, Simon; van Driel, Mieke; Henderson, Kim; Tapley, Amanda; McElduff, Patrick; Scott, John; Spike, Neil; Thomson, Allison; Magin, Parker
Abstract: Continuity of care is a defining characteristic of general practice. Practice structures may limit continuity of care experience for general practice registrars (trainees). This study sought to establish prevalence and associations of registrars' continuity of care. We performed an analysis of an ongoing cohort study of Australian registrars' clinical consultations. Primary outcome factors were 'Upstream' continuity (having seen the patient prior to the index consultation) and 'Downstream' continuity (follow-up organised post-index consultation). Independent variables were registrar, practice, patient, consultation and educational factors. 400 registrars recorded 48, 114 consultations. 43% of patients had seen the registrar pre-index consultation, and 49% had follow-up organised. 'Upstream' continuity associations included registrar seniority, Australian medical qualification, practice billing policy, smaller practice size, registrar's previous training in the practice, chronic disease and older, female patients (but not registrar full-time/part-time status). Associations of 'Downstream' continuity included non-Australian qualification, billing, chronic disease and the patient having seen the registrar previously. Consultations prompting follow-up were more complex: longer duration, involving more problems and generating more learning goals. There was, however, evidence for limited educational utility of this 'continuity'. In our study, continuity of care in Australian registrars' training experience is modest. Associations are complex, but may inform initiatives to increase in-training continuity.